The future of executive development - Moldoveanu, Mihnea C.; Narayandas, Das (Stanford Business Books, Stanford University Press, 2022)
"This book is an inquiry into the structure and dynamics of this very large and important industry and a map and guide to chief executive officers, chief talent officers, deans and university presidents on how to re-design their executive development programs in the near and far future"--